Investigating the role of FOSL2 and JUND in the molecular adaptation to hypoxia in colorectal cancer - Potgieter, Tammy (2023)
Colorectal cancer is a major cause of cancer-related death worldwide, overall ranking third in terms of cancer incidence but second in terms of cancer mortality. Many solid tumours including approximately one third of colorectal tumours feature regions of tumour hypoxia, or low oxygen. Tumour hypoxia arises due to the increased metabolic and proliferative rates of tumour cells, alongside the poor oxygen supply delivered through aberrant tumour neovasculature. Whilst once considered a mere consequence of tumour expansion, tumour hypoxia is now recognised as a driving force of malignancy, contributing to factors such as invasion, metastasis and therapy resistance. The HIF transcription factors are the canonical regulators of the transcriptional response to hypoxia. However, it is becoming increasingly recognised that many other transcription factors play a role in regulating the molecular adaptation to hypoxia, despite this network being under-investigated and not fully elucidated. Preliminary data suggests that the AP1 transcription factor plays an important role in mediating hypoxic colorectal cancer survival. In cancer, AP1 deregulation is implicated in many pathways including differentiation, proliferation and apoptosis. However, the role of AP1 in tumour hypoxia is not well understood. It was hypothesised that the AP1 subunits FOSL2 and JUND mediate crucial aspects of the hypoxic response in CRC. Both FOSL2 and JUND were found to be upregulated under hypoxic conditions, and knockdown of both subunits led to significantly reduced 3D spheroid volume and cell survival in a clonogenic assay. RNA-sequencing identified FOSL2 in particular as a novel regulator of the hypoxic transcriptional response, significantly associating with 333 hypoxia-inducible genes involved in processes such as tumour metabolism and invasion. FOSL2 was therefore taken forward to analyse clinical relevance, where FOSL2 expression was significantly correlated with pro-metastatic variables such as high tumour budding and an infiltrative tumour edge in a large CRC tissue micro array. However, FOSL2 was not a significant prognostic indicator for 5-year survival and FOSL2 knockdown did not significantly impact tumour growth in a sub-cutaneous in vivo model. Further work is needed to validate the role of FOSL2 in the hypoxic response.